Design and Implementation of a 2-input Arithmetic and Logic Unit using Quantum-dot Cellular Automata (Dhaka University Journal of Applied Science and Engineering, 2024)
Quantum-Dot-Cellular Automata (QCA), an emerging nanotechnology rooted in Coulomb repulsion, holds the ability to supplant orthodox complementary metal-oxide semiconductor (CMOS) technology. Its distinctive advantages lie in ultra-low power consumption, fast switching speed, and high-density structures. This study conducts an extensive literature review to introduce an Arithmetic and Logic Unit (ALU) based on QCA principles. The proposed QCA-based ALU incorporates fundamental logic gates, adders, and subtractors, leveraging the latest XOR gate. Utilizing simulation via QCA Designer 2.0.3, an in-depth performance evaluation of the model is conducted, comparing it with established ALUs based on metrics encompassing cell count, delay, and area. The findings showcase the efficiency of the proposed ALU, characterized by its minimal requirement of 277 cells, an area occupancy of 0.43 µm², and a delay of 2.75 clock cycles. This outcome highlights the favorable attributes of our design compared to existing alternatives, suggesting its potential contribution to the advancement of QCA-based digital circuitry.DUJASE Vol. 8 (1) 26-31, 2023 (January)